(untitled) (Journal of Management, 2020)
The main purpose of the research paper is to explore the consumer’s perception and satisfaction on shopping at Bhat Bhateni Super Market Biratnagar. The research study is based on descriptive research design and the sample is taken 30 among the infinite population visiting Bhat Bhateni Super Market Biratnagar by non-probability sampling under convenience sampling method. The data has been collected through primary source and questionnaire method has been used to know consumers perception and satisfaction. The data and informations are analysed and discussed with the help of percentage in tabular form by MS Excel. According to the results and discussion, consumers have perceived Bhat Bhateni Super Market as one of the convenient super market available in Biratnagar town. Consumers seems to be satisfied with the wide variety of product being offered, price and quality of those product, allocation arrangement of the product and many other services provided by Bhat Bhateni Super Market Biratnagar.